2017
DOI: 10.1155/2017/2812483
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chitosan Edible Coating on the Biochemical and Physical Characteristics of Carp Fillet(Cyprinus carpio)Stored at −18°C

Abstract: The effect of an edible coating (EC) with 1.5% chitosan as an additive, on common carp (Cyprinus carpio) fillet, was determined evaluating the biochemical, physicochemical, textural, microbiological, and nutritional characteristics periodically during its storage in the freezer (−18°C), observing a decrease in the rate of biochemical reactions related to degradation (p < 0.05), hydroperoxides content (HPC) (0.8324 nM hydroperoxides/mg of protein versus 0.5540 nM/mg with regard to the EC sample), as well as pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…A gelatin coat on fresh meat products should reduce lipid oxidation because the hydrogen bonds present in gelatin act as a barrier to oxygen (Antoniewski, Barringer, Knipe, & Zerby, 2007). On the other hand, Marggrander and Hofmann (1997) studied the lipid oxidation of gelatin coated fish and found lower level of MDA compared to uncoated sample. These authors attributed the protective effect of gelatin films to the presence of ionic functional groups, which create strong polymerfish interaction, resulting in good oxygen barrier properties.…”
Section: Lipid Oxidationmentioning
confidence: 99%
“…A gelatin coat on fresh meat products should reduce lipid oxidation because the hydrogen bonds present in gelatin act as a barrier to oxygen (Antoniewski, Barringer, Knipe, & Zerby, 2007). On the other hand, Marggrander and Hofmann (1997) studied the lipid oxidation of gelatin coated fish and found lower level of MDA compared to uncoated sample. These authors attributed the protective effect of gelatin films to the presence of ionic functional groups, which create strong polymerfish interaction, resulting in good oxygen barrier properties.…”
Section: Lipid Oxidationmentioning
confidence: 99%
“…Moreover, chitosan has been widely used to extend shelf life, quality, and sensory characteristics in many seafood products (Cao, Xue, & Liu, 2009;Cai et al, 2014). It has been reported that 2% (w/v) chitosan film retains the good quality characteristics and extends the shelf life of frozen silver carp (Fan et al, 2009), while 1.5% (w/v) edible chitosan coating improves the quality of frozen common carp fillet (Morachis-Valdez et al, 2017). Besides, 1% (w/v) chitosan glazing increases shelf life and quality of frozen skinless salmon (Oncorhynchus gorbuscha) fillets (Sathivel, Liu, Huang, & Prinyawiwatkul, 2007).…”
Section: A R T I C L E I N P R E S Smentioning
confidence: 99%
“…Chicken and fish meat is characterized as having a relatively high content of these kinds of fatty acid, more susceptible to oxidative deterioration compared to other kinds of meat (Maggioni et al, 2008;Morachis-Valdez et al, 2017).…”
Section: Physical-chemical Analysismentioning
confidence: 99%
“…The shelf life of the product can be reduced, leading to economic losses (Andrade et al, 2004;Mürmann et al, 2004;Conceição & Gonçalves, 2009;Dsimani et al, 2013;Morachis-Valdez et al, 2017).…”
Section: Introductionmentioning
confidence: 99%